Itens lexicais tabus: usá-los ou não. Eis a questão . - Orsi, Vivian [UNESP]; Zavaglia, Claudia [UNESP] (My University, 2012)
The language in use in a society is product of a culture and reflects the way a community thinks. Therefore, the lexical units, through the meanings assigned by a social group, establish a specific look of the universe. We intend to demonstrate that for the denomination of the sexual organs of the human body it usual to avoid the official anatomical terminology – relegated to contexts of great formality – and to adopt other lexical items during informal situations. We intend, with this research, to demystify some prejudices related to the erotic-obscene lexicon, its use and its creation, besides stimulating reflections, in Portuguese and Italian.

A língua em uso numa sociedade é produto de uma cultura e reflete o pensamento de um povo. Desse modo, as unidades léxicas, por meio dos significados atribuídos por um grupo social, determinam um olhar singular do universo. Intencionamos demonstrar que para a nomeação dos órgãos sexuais do corpo humano procura-se evitar a terminologia oficial, selecionada para contextos de grande formalidade, e empregar outras unidades léxicas em situações de maior informalidade. Almejamos, com esta pesquisa, desmistificar alguns preconceitos relacionados ao léxico erótico-obsceno, seu uso e sua criação, além de estimular reflexões sobre esse tema, em português e italiano.
Prohibited lexical items: “use them or not use them. That is the question
Keywords: léxico erótico-obsceno; metáfora; sociocultura; erotic-obscene léxicon; metaphor; socioculture